A mini review of electrochemical genosensor based biosensor diagnostic system for infectious diseases - Parmin, Nor Azizah; Hashim, Uda; Gopinath, Subash C.B.; Dahalan, Farrah Aini; Voon, C.H.; Uda, M.N.A.; Afnan Uda, M.N.; Rejali, Zulida; Afzan, Amilia; Jaapar, F. Nadhirah; Halim, F. Syakirah (Environmental and Toxicology Management, 2021)
The quest for alternative methods is driven by the need to provide expertise in real time in biological fields such as medicine, pathogenic bacteria and viruses identification, food protection, and quality control. Polymerase Chain Reaction (PCR) and Enzyme Linked Immunosorbent Assay (ELISA) are examples of traditional methods that have some limitations and lengthy procedures. Biosensors are the most appealing option because they provide easy, dependable, fast, and selective detection systems compared to conventional methods. This review provides an overview of electrochemical genosensor based biosensor diagnostic system for infectious diseases detection as well as their applications, demonstrating their utility as a fast and responsive tool for detecting pathogenic bacteria, viruses, GMOs, and human diseases.